Optimizing Islamic Education through Public Policy, Educational Politics, and Sharia Economics to Enhance the Quality and Self-Reliance of the Ummah - Hary Nurdi; Hamdan Hamdan; Syaifuddin Sabda; Husnul Yaqin (Integrated Education Journal, 2025)
This study aims to analyze how optimizing Islamic education can be achieved through the integration of public policy, educational politics, and Islamic economics as strategic efforts to improve the quality and independence of the Muslim community. The research method used is library research, involving data collection from books, scientific journals, policy reports, and official documents. A descriptive–qualitative analysis was applied to identify the relationship between structural elements of education and relevant Islamic economic mechanisms. The findings reveal that Islamic education becomes more effective when supported by favorable public policies, stable education politics, and sustainable Islamic economic-based funding. The synergy of these three aspects strengthens Islamic educational institutions and enhances learners’ capabilities in responding to modern socio-economic challenges